2013
DOI: 10.1155/2013/694171
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Based Multiscale Model for Electromagnetic Analysis in the Human Head with Implanted DBS

Abstract: Deep brain stimulation (DBS) is an established procedure for the treatment of movement and affective disorders. Patients with DBS may benefit from magnetic resonance imaging (MRI) to evaluate injuries or comorbidities. However, the MRI radio-frequency (RF) energy may cause excessive tissue heating particularly near the electrode. This paper studies how the accuracy of numerical modeling of the RF field inside a DBS patient varies with spatial resolution and corresponding anatomical detail of the volume surroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 65 publications
0
28
0
Order By: Relevance
“…Using a large memory (1.5 TB), 30 processors machine, the EM simulation step was ~6 hours for all DBS models simulated in this. This is an order or magnitude faster than simulation times reported by other authors who used FDTD (the reported simulation times for this type of problem with FDTD are 24–48 hours, even when using GPU acceleration (Iacono et al , 2013; Cabot et al , 2013)).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Using a large memory (1.5 TB), 30 processors machine, the EM simulation step was ~6 hours for all DBS models simulated in this. This is an order or magnitude faster than simulation times reported by other authors who used FDTD (the reported simulation times for this type of problem with FDTD are 24–48 hours, even when using GPU acceleration (Iacono et al , 2013; Cabot et al , 2013)).…”
Section: Discussionmentioning
confidence: 68%
“…This is due to electromagnetic (EM) coupling between the MRI radiofrequency (RF) coil and the DBS metallic leads (Yeung and Atalar, 2001; Finelli et al , 2002; Park et al , 2005; Park et al , 2007; Angelone et al , 2008; Neufeld et al , 2009; Bottomley et al , 2010; Acikel and Atalar, 2011; Eryaman et al , 2011; Bonmassar et al , 2013; Iacono et al , 2013; Acikel et al , 2016; Golestanirad et al , 2016a). As a result, MRI is seldom used in DBS patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] imaging (CDI) methods, which can image the electrical current pathway by injected currents, was proposed by using a clinical MRI scanner. 7,9,11 This method measures the magnetic flux density (B) induced by the injection current, and recovers the corresponding current density distribution of J = (J x , J y , J z ) from the Ampere law J = (1/µ 0 )∇ × B, where µ 0 is the magnetic permeability of free space.…”
Section: Deep Brain Stimulation (Dbs)mentioning
confidence: 99%
“…One unilateral implant was modeled as an insulated lead with an array of four cylindrical electrode contacts at the distal tip [11]. The contacts were modeled as conductive cylindrical rings (1.5mm in height, 1.27mm in external diameter, 0.8mm internal diameter) separated by fully insulated cylinders (1.5mm in height, 1.27mm diameter) (Fig.…”
Section: Model Of Implantmentioning
confidence: 99%